1991
DOI: 10.1002/ijc.2910490522
|View full text |Cite
|
Sign up to set email alerts
|

Infection of rats with HTLV‐1: A small‐animal model for HTLV‐1 carriers

Abstract: A human T-cell line producing human T-cell leukemia virus type I (HTLV-I), MT-2, was injected intravenously into female F344 rats aged 5 weeks to make HTLV-I carrier rats. Antibody against HTLV-I was detected at the 5th week after MT-2 injection, and its titer reached a high plateau which continued from the 15th to the 27th week. The antibodies were against p19, p24, p28 and p53 of HTLV-I antigens from MT-2 cells. The gag, pX and LTR nucleotide sequences of HTLV-I provirus were demonstrated by using polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 24 publications
1
53
1
Order By: Relevance
“…Experimental infection of rats with HTLV-1 was first established in 1991 (Suga et al, 1991). Although initial experimental infection was achieved with F344 rats, it was later established that there was considerable differences in the response of various rat strains to HTLV-1 infection (Ishiguro et al, 1992;Kushida et al, 1993;Ibrahim et al, 1994).…”
Section: Rat Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental infection of rats with HTLV-1 was first established in 1991 (Suga et al, 1991). Although initial experimental infection was achieved with F344 rats, it was later established that there was considerable differences in the response of various rat strains to HTLV-1 infection (Ishiguro et al, 1992;Kushida et al, 1993;Ibrahim et al, 1994).…”
Section: Rat Modelsmentioning
confidence: 99%
“…Over the past 25 years, a variety of animal models of HTLV-1, infection and transformation have provided fundamental information about viral and host determinants of this devastating malignancy (Table 1). The virus consistently infects rabbits (Akagi et al, 1985;Lairmore et al, 1992), some non-human primates (Nakamura et al, 1987;Murata et al, 1996), and to a lesser extent rats (Suga et al, 1991;Ibrahim et al, 1994). Viral transmission in mice using typical methods of infection produces inconsistent infections and limited virus expression in tissues (Fang et al, 1998;Feng et al, 2001;Furuta et al, 2002a, b;Nitta et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, rabbit (Akagi et al, 1985;Zhao et al, 2002), rat (Suga et al, 1991;Ishiguro et al, 1992) and mouse (Fang et al, 1998;Tanaka et al, 2001) models of persistent HTLV-1 infection have been reported. In all these models, HTLV-1 was detected in a large spectrum of hematopoietic cell types and nonhematopoietic tissues, including brain, lung, kidney, heart, liver, thyroid, as well as thymic and endometrium epithelia, depending on the model and the timing of the inoculation.…”
Section: Animal Models: a Broad In Vivo Tropismmentioning
confidence: 99%
“…This will require the development of a small animal model that can be exploited as a tool for the screening and evaluation of HTLV-1 infection. However, although HTLV-1 consistently infects rabbits [2,3], some non-human primates [4,5], and to a lesser extent, rats [6,7], the virus does not efficiently infect murine cells. Previous studies have indicated that viral transmission in mice, using typical methods of infection, results in inconsistent infections and limited virus expression in tissues [8][9][10].…”
Section: Resultsmentioning
confidence: 99%